Diseño y construcción de una máquina automática para la elaboración de bloques artesanales del barrio La Calera para la parroquia Eloy Alfaro cantón Latacunga año 2012. - Andrade Lema, Segundo Gabriel (2014)
To this project we had to design and proceed to build an automatic block making pumice, in order to facilitate the work, improve product quality and production about manually manufacturing so that to improve the life quality of limekiln artisanal sector at La Calera neighborhood of Latacunga Canton, Cotopaxi province. Basic skills to develop this project were acquired in La Calera Limekiln artisanal sector of Latacunga Canton, Cotopaxi province where still work by manual and rudimentary processes. The manual block making machines have been used to collect, select, adapt, redesign and implement some mechanisms and systems for a better alternative in our automatic machine building. As a result, we used a vibration system and oil hydraulic power system to: feed mixture, the stripping, and compression. To control and automation of different processes used a SIEMENS LOGO. Upon completion of testing it was found that the implementation of these systems, the product is obtained in less time. Final production obtained with this machine is approximately 650 blocks per hour. It is recommended that in the future for implementation of this project will make an mixer and lift implementation, bringing the mixture will be obtained in less time and with better dosing, and get further increase the production capacity of the machine.